2021
DOI: 10.1002/pmic.202100004
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Giardia lamblia and Trichomonas vaginalis flagella reveal unique post‐translational modifications in tubulin that provide clues to regulation of their motilities

Abstract: All eukaryotic flagella are made of microtubules and driven by dynein motor proteins. However, every organism is unique in terms of its flagellar waveform, beat frequency, and its general motility pattern. With recent research, it is becoming clear that despite overall conservation in flagellar structure, the pattern of tubulin post‐translational modifications within the flagella are diverse and may contribute to variations in their patterns of motility. In this study, we have analyzed the tubulin post‐transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Cytoskeleton proteins of Giardia are closely related to its pathogenicity. The α-tubulin and β-tubulin could form heterodimers, the two main types of tubulin-forming microtubules ( 36 ). Microfilaments in the cytoskeleton related to encystation are formed by actin, which is part of the globular multifunctional protein family ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoskeleton proteins of Giardia are closely related to its pathogenicity. The α-tubulin and β-tubulin could form heterodimers, the two main types of tubulin-forming microtubules ( 36 ). Microfilaments in the cytoskeleton related to encystation are formed by actin, which is part of the globular multifunctional protein family ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, Giardia intestinalis can cause host diarrhoea through mechanisms such as shortening of the microvillous brush border, causing indigestion and impaired absorption, increased intestinal transit rate and excessive anion secretion [21]. These mechanisms are closely related to Giardiamediated caspase-dependent cellular regulation and disruption of intestinal epithelial tight junctions.…”
Section: Structural Disruption and Dysfunction Of The Intestinal Epit...mentioning
confidence: 99%
“…Future proteomic studies on G. duodenalis may also focus on investigating the post-transcriptional regulation of this parasite, especially on translational inhibition relating to Giardia ’s Pumilio homology proteins (Puf), which may have a crucial role in the encystation of this parasite [ 68 ]. With the completion of a comprehensive molecular map of histone modifications in Giardia by Emery-Corbin et al (2021) [ 64 ], chromatin proteomics may achieve the mapping of previously reported non-histone proteins, such as tubulin [ 69 ] and cyclin B [ 70 ], by using quantitative MS profiling to confirm their dynamic variations in regulation during parasite development. Ideally, proteomics research should be linked with experimental approaches to move beyond protein identification and progress to the in vitro or in vivo investigation of these proteins as players in pathogenesis, virulence, and metabolism, and later to the validation of their role as biomarkers or drug and vaccine targets that can lead to new tools with which to control giardiasis.…”
Section: Future Directionsmentioning
confidence: 99%